Incomplete Democracies in the Asia-Pacific Evidence from Indonesia, Korea, the Philippines and Thailand - Dore, Giovanna Maria Dora.; Ku, Jae H.; Jackson, Karl D. (Critical Studies of the Asia-Pacific Series, 2014)
This collection presents a varied picture of the state of democracy in Asia, revealing unique findings from a project entitled the 'Asia Democracy Initiative' which explored the role of ordinary people in democratization through the rise of expressive social values in Indonesia, South Korea, the Philippines and Thailand.